Vascular smooth muscle cell dysfunction contribute to neuroinflammation and Tau hyperphosphorylation in Alzheimer disease - Aguilar-Pineda, Jorge A. (2021)
This research was funded by Consejo Nacional de Ciencia, Tecnologia e Innovacion Tecnologica de Peru (grant N~ 024-2019-Fondecyt-BM-INC.INV and CONCYTEC-FONDECYT-E038-01).